Analysis of Urban Farming Success Determinants - Novitasari, Rafitri; Wahyuningtyas, Agustina Shinta Hartati; Dewi, Heptari Elita; Isaskar, Riyanti (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 19 No 1 (2025)DO - 10.24843/SOCA.2025.v19.i01.p05, 2025)
Malang City experiences an increase in population every year, which has led to a reduction in agricultural land. In addition, the population continues to grow due to the arrival of newcomers and students from outside the city. Despite having a high population, there is still unused agricultural land that has not been optimally utilized. These areas have transitioned to urban farming by using the land to produce healthy vegetables. This study aims to analyze the factors influencing interest in agriculture, such as knowledge, attitude, and perception. A quantitative approach was used in this research, employing purposive sampling techniques, including interviews and documentation. The total sample size in this study was 70 respondents. Data processing was conducted using descriptive statistical analysis and SEM-PLS. The results of the study indicate that knowledge and attitude toward urban agriculture do not have a significant effect on people’s interest in farming in urban areas. However, perception of urban agriculture has a positive influence on interest, as the community recognizes its economic, social, and environmental benefits.